THE EFFECT OF NEW MEDIA ON CONTEMPORANEITY OF THE WORKS BY KRZYSZTOF WODICZKO - Sepideh Takshi; Mohammad Kazem Hassanvand (PalArch's Journal of Archaeology of Egypt / Egyptology, 2021)
Attentions were paid to media since the second half of the twentieth century and it was with the technological progresses that the number of the media was increased and a vast ground was in addition set for the artists to grant a power of manifestation to their ideas. The present study aims at finding an answer to the question as to how have the new media influenced the contemporaneity of the works by artists, especially Krzysztof Wodiczko? In order to find an answer to this question, the definition and specifications of contemporaneousness should be studied and investigated hence it is proposed that how much have media influenced contemporaneity of the works by various artists. Considering the study, technological progresses and the application of the new media, especially of the digital type, have enabled more interaction between the audience and the artworks to the extent that the former is no longer just an observer; thus, contemporaneity of the artworks is not specific to the time in a historical sense and numerous factors have caused the artworks to become contemporaneous; media are amongst these factors. The present descriptive-analytical research tries studying and defining the aforesaid indicators; the works by Krzysztof Wodiczko will be also analyzed in the end.